Privacy in Modern China - McDougall, Bonnie S. (History compass, 2004)
Despite a common belief that ‘the Chinese’ have no concept of privacy, there is a well-established tradition of private property and privacy values in traditional and modern China. In the twentieth century, rhetoric on the public good generally prevailed over individualism and subjectivity, but privacy practices, especially within the family, persisted despite the state's intrusions into private life. Both privacy and private property were re-evaluated in the post-Mao era, giving rise to a new appreciation of privacy functions and values.